Emotion elicitation: a comparison of pictures and films - Uhrig, Meike; Baumgärtner, Ulf; Treede, Rolf-Detlef; Henrich, Florian (Frontiers in psychology, 2016)
Pictures and film clips are widely used and accepted stimuli to elicit emotions. Based on theoretical arguments it is often assumed that the emotional effects of films exceed those of pictures, but to date this assumption has not been investigated directly. The aim of the present study was to compare pictures and films in terms of their capacity to induce emotions verified by means of explicit measures. Stimuli were (a) single pictures presented for 6 s, (b) a set of three consecutive pictures with emotionally congruent contents presented for 2 s each, (c) short film clips with a duration of 6 s. A total of 144 participants rated their emotion and arousal states following stimulus presentation. Repeated-measures ANOVAs revealed that the film clips and 3-picture version were as effective as the classical 1-picture method to elicit positive emotions, however, modulation towards positive valence was little. Modulation toward negative valence was more effective in general. Film clips were less effective than pictorial stimuli in producing the corresponding emotion states (all p < .001) and were less arousing (all p ≤ .02). Possible reasons for these unexpected results are discussed.
Gesehen am 08.02.2019